Memorable Experience of Couples’ Trips - Coelho,Mariana de Freitas (2018)
Abstract The tourism experience is a term which is associated with multiple interpretations that permeate the environment, people and other components of the activity. The objective of this article is to identify the essence of memorable leisure trips of couples, considering that the trip of couples is still little studied. "Couples" is understood as a broad term, consisting of individuals who have a romantic and/ or sexual relationship, such as lovers, legally married persons (spouses), GLBT public, and individuals of different ages and lifestyles. The work method is qualitative and exploratory, composed of three different and complementary studies. The first study included stories of two couples during their travel experience. The second study is composed of narratives of couple trips described by one of the parts of the pair, with semi structured script. The third study covered in-depth interviews with couples who were older than 18 years and traveled for leisure at least once in the 12 months prior to the date of data collection. The data analysis was done through content analysis, through thematic categorization of the text. The results show that the couple trip provides the creation of memorable events, in which the stories and situations lived can be shared later between the couple and their acquaintances. In addition to routine escape, fun and relaxation, commemorative dates and passions in common are also motivating for the couple's travels. Thus, tourism destination organizations should identify common interest of the couple to better serve them. The contributions of the study refer to the group experience approach rather than the individual perspective.